Systematic overview of the preparation, interface characteristics, strengthening mechanisms, and challenges of graphene-reinforced Al matrix composites - Yunlei Wang; Fangzhou Yang; Taibin Wu; Guangjie Huang (Journal of Materials Research and Technology)
Graphene has become one of the ideal reinforcements for Al matrix composites due to its unique two-dimensional (2D) structure and excellent comprehensive performance. With the development of the application of Al matrix composites and their preparation technology, graphene-reinforced Al matrix composites (GRAMCs) have gradually become a research hotspot in terms of structural lightweighting and material performance modification. Owing to the agglomeration of reinforcements, poor interface bonding and the occurrence of interface reactions will seriously affect the comprehensive performance of Al matrix composites, thus restricting the development and application of GRAMCs. With regards to this, it comprehensively summarizes the existing preparation methods of GRAMCs, focusing on the interface bonding, interface reaction, and tribological properties of its composites. It also analyzes the typical strengthening mechanism produced by graphene as a reinforcement, and proposes the application prospects, future challenges and corresponding solution of GRAMCs, in the hope of providing a practical and reliable development path for the future large-scale industrial production and application of high-performance GRAMCs.